Chăm sóc bệnh nhân ung thư đại trực tràng được hoá trị tại bệnh viện Trung ương Huế - Hạnh, Phạm Thị Hồng; Hoa, Châu Thị; Trang, Nguyễn Thị Diệu; Phượng, Trần Thị Kim; Yến, Đỗ Thị; Bích, Võ Thị Hồng; Yến, Trương Thị Kim (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
A